Preoperative muscle function assessments in nursing as predictors of postoperative outcomes in patients with colorectal cancer and malnutrition - Xie, Tingting; Li, Jiang; Wu, Xiaofen; Yang, Xiangxiang; Wang, Minmin; Dong, Qiantong; Chen, Xiaolei; Chen, Weizhe; Zheng, Xiuyun (Frontiers in Nutrition, 2025)
BackgroundPatients with colorectal cancer (CRC) often present with malnutrition upon admission, which is associated with a poor prognosis. However, current traditional tools for diagnosing malnutrition do not assess muscle function. This study aims to explore whether the evaluation of muscle function has predictive value for the prognosis of CRC patients with malnutrition.MethodsWe retrospectively analyzed the clinical parameters of patients with CRC and malnutrition based on the Global Leadership Initiative on Malnutrition criteria who underwent radical surgery at our center from 2015 to 2021. Patients were grouped according to their preoperative muscle function assessments. The clinical characteristics and postoperative outcomes were compared between the groups. The risk factors for postoperative complications were analyzed.ResultsA total of 346 patients were included in the study. Patients with low handgrip strength had higher incidences of total (p = 0.001), surgical (p = 0.015) and medical (p = 0.024) complications and longer postoperative hospital stays (p = 0.026). Patients with low gait speed had higher incidences of total (p = 0.027) and medical (p = 0.004) complications. Low handgrip strength was an independent risk factor for total (p = 0.008) complications, surgical (p = 0.038) complications and overall survival (p = 0.003). Low gait speed was an independent risk factor for medical complications (p = 0.021).ConclusionFor malnourished CRC patients, preoperative assessment of muscle function during perioperative care can predict adverse postoperative outcomes and can be incorporated into a comprehensive nutritional management plan.